Effect of Blood Pressure Lowering in Early Ischemic Stroke. Issue 7 (July 2015) - Lee, Meng; Ovbiagele, Bruce; Hong, Keun-Sik; Wu, Yi-Ling; Lee, Jing-Er; Rao, Neal M.; Feng, Wayne; Saver, Jeffrey L.
<x xml:space="preserve">Abstract</x> Background and Purpose— Elevated blood pressure is common in acute stage of ischemic stroke and the strategy to manage this situation is not well established. We therefore conducted a meta-analysis of randomized controlled trials comparing active blood pressure lowering and control groups in early ischemic stroke. Methods— Pubmed, EMBASE, and Clinicaltrials.gov from January 1966 to March 2015 were searched to identify relevant studies. We included randomized controlled trials with blood pressure lowering started versus control within 3 days of ischemic stroke onset. The primary outcome was unfavorable outcome at 3 months or at trial end point, defined as dependency or death, and the key secondary outcome was recurrent vascular events. Pooled relative risks and 95% confidence intervals were calculated using random-effects model. Results— The systematic search identified 13 randomized controlled trials with 12 703 participants comparing early blood pressure lowering and control. Pooling the results with the random-effects model showed that blood pressure lowering in early ischemic stroke did not affect the risk of death or dependency at 3 months or at trial end point (relative risk, 1.04; 95% confidence interval, 0.96–1.13; P=0.35). Also, blood pressure lowering also had neutral effect on recurrent vascular events, as well as on disability or death, all-cause mortality, recurrent stroke, and serious adverse events. Conclusions— This meta-analysis suggested blood pressure lowering in early ischemic stroke had a neutral effect on the prevention of death or dependency.